The Community Empowerment Program to Reduction Poverty in Banjar - Tete Saepudin; Acuviarta A (Faculty of Economics and Business, University of Pasundan, 2016)
This study aims to generate key strategies of sector development community empowerment to reduction poverty in Banjar. The analysis uses SWOT presented in three parts: SAP (Strategic Advantages Profile), ETOP (Environmental Threats and Opportunity Profile), and SWOT Matrix. The analysis showed the government’s attention to the program that was launched (district development program and the urban poverty program) where is by provision of Counterpart Funds from APBD has been increasing steadily every year. The mechanism has been implemented according to some regulations. The urban empowerment program should further focus and involve on the interests and needs of urban communities. The obstacles faced on the research to determine the program are, the execution (based onmain interest), the lack of human resources who understand and the plan ownership in preparing programs of community development and the lack of human resources with reliability in manufacturing reporting on the program implementation.